Fast, Microwave-Promoted One-Pot Synthesis of Bicyclic Pyrimidones from Baylis-Hillman Adducts. (February 2015) - Liu, Yongliang; Wan, Kun; Wang, Zengxue
Two types of fused pyrimidones, 3-substituted-7-chloro-4H -pyrimido[1, 2-b]pyridazin-4-ones and 6-substituted-5H-thiazolo-[3, 2-a]pyrimidin-5-ones were easily prepared from Baylis-Hillman adduct acetates under microwave irritation in high yields.